2015
DOI: 10.1016/j.ymben.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of heterologous transporters in Saccharomyces cerevisiae and identification of important amino acids for xylose utilization

Abstract: Efficient and specific transporters may enhance pentose uptake and metabolism by Saccharomyces cerevisiae. Eight heterologous sugar transporters were characterized in S. cerevisiae. The transporter Mgt05196p from Meyerozyma guilliermondii showed the highest xylose transport activity among them. Several key amino acid residues of Mgt05196p were suggested by structural and sequence analysis and characterized by site-directed mutagenesis. A conserved aromatic residue-rich motif (YFFYY, position 332-336) in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 56 publications
1
86
0
3
Order By: Relevance
“…A similar mutant transporter (Gal2p-N376V) that can transport both glucose and xylose without glucose repression was also identified [14 ]. Recently, two independent groups found that mutations Hxt36p-N367 [46] and Mgt05196p-N360F [35] in the arginine residue of other sugar transporters resulted in improved transport of xylose without glucose repression. The isolation of the mutant hexose transporters capable of transporting xylose without glucose inhibition was a crucial step towards simultaneous co-fermentation of glucose and xylose.…”
Section: Current Opinion In Chemical Biologymentioning
confidence: 96%
See 1 more Smart Citation
“…A similar mutant transporter (Gal2p-N376V) that can transport both glucose and xylose without glucose repression was also identified [14 ]. Recently, two independent groups found that mutations Hxt36p-N367 [46] and Mgt05196p-N360F [35] in the arginine residue of other sugar transporters resulted in improved transport of xylose without glucose repression. The isolation of the mutant hexose transporters capable of transporting xylose without glucose inhibition was a crucial step towards simultaneous co-fermentation of glucose and xylose.…”
Section: Current Opinion In Chemical Biologymentioning
confidence: 96%
“…Heterologous transporters with higher affinities for xylose over glucose were identified. These transporters include Gxs1p from Candida intermedia [33], Xut3p from S. stipitis [34], and Mgt05196p from Meyerozyma guilliermondii [35]. Also, heterologous overexpression of STP2 from Arabidopsis thaliana and ARAT from S. stipitis in S. cerevisiae led to improved anaerobic L-arabinose fermentation, especially at low Larabinose concentrations.…”
Section: Metabolic Engineering For the Utilization Of Non-glucose Sugarsmentioning
confidence: 99%
“…Normally, xylose is absorbed non-specifically and insufficiently by hexose transporters and is competitively inhibited by glucose in S. cerevisiae (Subtil and Boles 2012). Therefore, to address this problem, both wild-type and mutated endogenous and heterologous transporters were screened (Diao et al 2013; Farwick et al 2014; Moon et al 2013; Nijland et al 2014; Runquist et al 2009; Shin et al 2015; Wang et al 2015, 2016). Moreover, with higher efficiency and/or specificity for xylose, a transporter lacking glucose inhibition may relieve the glucose repression effect in a xylose absorption node, thereby increasing xylose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with higher efficiency and/or specificity for xylose, a transporter lacking glucose inhibition may relieve the glucose repression effect in a xylose absorption node, thereby increasing xylose metabolism. Recently, we found the mutant MGT05196 N360F , which is derived from the Meyerozyma guilliermondii transporter gene MGT05196 and exhibits xylose-specific transport and no glucose inhibition (Wang et al 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation